Integrating Local Culture into Foreign Language Learning through Humour: A Systematic Literature Review - Arief, Yusuf Al (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2024)
This systematic literature review explored the incorporation of local culture into foreign language learning through humour, a topic of interesting relevance in language education. The research showed the shift from traditional language teaching methods to using humour and cultural elements to improve learning outcomes. Additionally, the method used during the research was a systematic review of forty-three scientific articles, focusing on publications ranging from 2017 to 2024 to ensure the results as well as implications were up-to-date and reliable. The result of the finding showed how these elements were effectively incorporated into foreign language teaching practices to promote language acquisition as well as understanding of culture. This research signified the importance of humour in conveying cultural nuances and improving intercultural competence. The finding also signified that incorporating local culture through humour increased language proficiency, cultivated appreciation of students concerning different cultures, and promoted intercultural communication skills. This research provided valuable insights for educators to develop innovative language teaching strategies that would create engaging and rich learning environments for language students. Future research should focus on exploring long-term impacts of using humour and incorporating local culture on the intercultural competence of students. Additionally, examining the application of the method across different age groups, proficiency levels, and cultural contexts would be recommended. Further results could investigate the role of technology in increasing the use of humour and culture incorporation in language education.